Device and Measuring Method the Moments of Rolling Resistance Forces on the Contact Spot - I. Z. Gilavdary; S. Mekid; N. N. Riznookaya (Приборы и методы измерений)
Currently, the study of rolling friction is one of the main directions in the study of the laws of contact interaction of solids. The complexity of solving the problems existing in this area is evidenced by the practically vast number of publications, the list of which is constantly growing.In this paper, attention is paid to studies of the moments of rolling resistance at displacements from the equilibrium position of a ball-shaped body that are substantially smaller than the size of the contact spot. The purpose of the present work is to describe the design of the single-contact pendulum device developed by the authors, in which the physical pendulum, resting on the flat surface of the body under study with only one ball, makes free small stable swings in a vertical plane, as well as in the description of a special measurement technique with high sensitivity and accuracy rolling resistance forces, including adhesion forces and frequency-independent forces of elastic deformations. It is assumed that the adhesion forces can exhibit both dissipative properties and elastic properties, while elastic forces are independent of the strain rate.The originality of the method of measuring rolling resistance in this paper consists in using the method of nonlinear approximation of the dependence of the amplitude and period of swing of the pendulum on time. The approximation is carried out on the basis of the proposed laws of amplitude decay and period variation, which differ from the usual exponential law.It is assumed that this approach allows one to evaluate the surface tension of a solid and evaluate the pressure of adhesion forces between the surfaces of the contacting bodies, as well as to establish an analytical form of the moment of rolling resistance. The curves of the dependence of the rolling resistance moment on the swing amplitude of the pendulum are constructed. Experiments were performed for the following pairs of contacting bodies: steel-steel, steel-glass, steel-electritechnical silicon. It was assumed that the pressure at the contact spot did not exceed the elastic limit.The developed single-ball pendulum device and the proposed measurement procedure open up new wide possibilities for studying the laws of mechanisms of rolling resistance under conditions of microand mesoscale displacements of a rolling body from a state of rest.